2019
DOI: 10.1371/journal.pone.0219163
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Salmonella enterica serovar Enteritidis exposed to ethanolic extract of organic cranberry pomace

Abstract: Non-typhoidal Salmonella enterica serovars continue to be an important food safety issue worldwide. Cranberry ( Vaccinium macrocarpon Ait ) fruits possess antimicrobial properties due to their various acids and phenolic compounds; however, the underlying mechanism of actions is poorly understood. We evaluated the effects of cranberry extracts on the growth rate of Salmonella enterica serovars Typhimurium, Enteritidis and Heidelberg and on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Fruits of large cranberry and their preserves (juices, infusions, teas, and pomace) are readily consumed as functional food due to their broad spectrum of properties that are beneficial for health, such as reduced risk of cancers [ 11 ] and cardiovascular diseases [ 12 ], general antimicrobial activity [ 13 ], and specific antimicrobial activity towards pathogens in the urinal tract (inhibits bacterial adhesion) [ 14 ], as well as antimutagenic, anti-inflammatory, and anti-hypercholesterolemic activities [ 15 ]. Additionally, large cranberry fruit juice has been used to treat digestive tract disorders [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fruits of large cranberry and their preserves (juices, infusions, teas, and pomace) are readily consumed as functional food due to their broad spectrum of properties that are beneficial for health, such as reduced risk of cancers [ 11 ] and cardiovascular diseases [ 12 ], general antimicrobial activity [ 13 ], and specific antimicrobial activity towards pathogens in the urinal tract (inhibits bacterial adhesion) [ 14 ], as well as antimutagenic, anti-inflammatory, and anti-hypercholesterolemic activities [ 15 ]. Additionally, large cranberry fruit juice has been used to treat digestive tract disorders [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of genome technologies, the study of S. typhimurium by transcriptome analysis is increasing. Das et al studied transcriptome changes of S. typhimurium after treatment with cranberry extract and found that the expression of several pathogenicity-related genes, including ssaT on virulence island II, were significantly downregulated [22]. SPI2, which encodes T3SS2, plays an important role in the survival and pathogenicity of S. typhimurium in host cells [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of cranberry extract and antimicrobial proteins on the growth rates and transcriptomics of S. typhimurium were investigated. The expressions of related genes, such as those involved in iron acquisition, flagella, energy metabolism, pathogenicity, virulence islands and the cell membrane, were significantly downregulated after bacteriostatic treatment in S. typhimurium [22,23]. According to Song et al and Wang et al [24,25], the transcriptome was used to explore the mechanism of antibacterial activity of BITC on Vibrio parahaemolyticus and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Unless the material used in any given study was fully purified and structurally characterized by NMR spectroscopy, it must be assumed that multiple components beyond those discussed by the researchers could be contributing to the observed biological effects, including oligosaccharides and other compounds. In spite of this, many studies continue to attribute observed biological effects primarily to polyphenols, flavonoids, and other phenolic compounds [132,149,155,288,308]. Some studies have even directly reported carbohydrate contents as high as 95% for their materials and yet still discuss their results in the context of the more readily detectable and more frequently characterized anthocyanins, flavonols, organic acids, and PACs [308].…”
Section: Recognized Composition Influences Bioactivity Interpretationsmentioning
confidence: 99%
“…In spite of this, many studies continue to attribute observed biological effects primarily to polyphenols, flavonoids, and other phenolic compounds [132,149,155,288,308]. Some studies have even directly reported carbohydrate contents as high as 95% for their materials and yet still discuss their results in the context of the more readily detectable and more frequently characterized anthocyanins, flavonols, organic acids, and PACs [308]. This type of bias towards flavonoids and polyphenolic compounds as the primary significant biological components of cranberries may predispose other researchers to avoid considering additional possible explanations for their results and further delay overall progress for future investigations of cranberry bioactivity.…”
Section: Recognized Composition Influences Bioactivity Interpretationsmentioning
confidence: 99%